THE ROLE OF THE INTENTION OF THE REGISTRATION OF NEW PROSPECTIVE STUDENTS ON THE DECISION TO RE-REGISTER BECOME A STUDENT OF INDONESIAN POS POLYTECHNIC, BANDUNG - Rahardjo, Panggih (Dinasti Publisher, 2021)
The study wanted to prove the role of the intention of the list of prospective new students on the decision to re-register as a student at the Bandung Pos Indonesia Polytechnic. The total population of 800 new students in 2020-2021, the sample was determined using the Slovin formula with a total of 100 people. The results showed that all data from the variable intention to register new students and the decision to re-register as a student were declared valid and reliable. The corrected item-total correlation data for the variable data of intention to register new students is between 0.310 -0.645 smaller than 0.300. So it is declared valid. so declared valid. The Cronbach's Alpha value for the variable intention to register new students and the variable for the decision to re-enroll as a student is 0.802 and 0.929, respectively, which is greater than 0.700, so it is declared reliable. This means that the questionnaire used to collect data is a quality questionnaire and meets the requirements to collect data. The data proved to be normally distributed with asymp.sig values ??of 0.144 and 0.079. The simple linear regression equation is Y = a + b X .Y = 44.145 + 2.817 X. The meaning of this simple linear regression equation is: If without Intention to register a prospective new student, the value of Decision to register as a student is only 44.145. If plus one unit of Intention to register a prospective new student, then the value of Decision to register as a student which was originally only 44.145 will increase to 44.145 + 2.817 = 46.962.. So to increase Decision to register as a student it is necessary to increase Intention to register prospective new students. The author has proven that the Intention to register a prospective new student affects the Decision to register as a student positively and significantly, the t-test value is 20,581 > the t-table value for 100 respondents according to Junaidi (2020:8) of 0.67. The calculated significance value is 0.67. 0.000 < 0.05